PERAN MASYARAKAT DALAM SARANA DAN PRASARANA UNTUK PENINGKATAN MUTU PENDIDIKAN DI SDIT CAHAYA HATI BUKITTINGGI - Rahma Dona; Rahma Yanti; Darul Ilmi (CV. ADIBA AISHA AMIRA, 2024)
This research aims to analyze and identify educational facilities and infrastructure at SDIT Cahaya Hati Bukittinggi, based on superior schools that have been accredited A in Bukittinggi City. This research uses a qualitative descriptive research method. Data collection techniques are through observation, interviews. Sources of data obtained for research were from school principals, the community and parents, representatives of student guardians, TU staff. Based on the results of the research, it shows that SDIT Cahaya Hati Bukittinggi has a total of 34 rooms, including 18 classrooms from grades 1-6, 1 library, 2 prayer rooms, 1 uks, office space for the principal and TU staff, educational board room and foundation treasurer's room, TPQ room, sports facilities warehouse and hall for school events and other rooms needed to support educational activities at Cahaya Hati Elementary School, Bukittinggi. Looking at the condition of the school building, it is very good and makes students comfortable studying, ustdz and ustdzah are also comfortable in teaching, sports and worship facilities are very adequate and have sufficient water source capacity and all of this cannot be separated from the contribution and support from the community in improving school facilities and infrastructure. From the data above, it can be seen that SDIT Cahaya Hati Bukittinggi has met 85% of the infrastructure standards that have been set, but there is a lack of space for the science laboratory and prayer facilities which are still not optimal because they still use classrooms for every practical activity of midday prayer and noon prayer. congregation. Furthermore, the role of the community for schools is very necessary, both morally and materially, in efforts to develop facilities and infrastructure, namely by renovating school buildings as an effort to develop and maintain school infrastructure to support effective and efficient teaching and learning activities at Cahaya Hati Elementary School, Bukittinggi